A heterogeneous copper(I)-catalyzed aerobic oxidative cross-dehydrogenative coupling of terminal alkynes with thiols leading to alkynyl sulfides. Issue 46 (18th November 2015) - Fang, Zhiqiang; He, Wen; Cai, Mingzhong; Lin, Yang; Zhao, Hong
Graphical abstract: A simple and practical method for a selective synthesis of alkynyl sulfides has been developed through the direct oxidative cross-dehydrogenative coupling of terminal alkynes with thiols in DMSO using a recyclable MCM-41-supported bidentate nitrogen copper(I) complex [MCM-41-2N-CuCl] as catalyst under an atmosphere of oxygen. Highlights: The MCM-41-2N-CuCl complex can be easily prepared by a simple two-step procedure. Heterogeneous Cu-catalyzed CDC reaction of 1-alkynes with thiols is first reported. The reaction generates selectively a variety of alkynyl sulfides in high yields. The Cu catalyst can be recycled 10 times without any decrease in activity. Our catalytic system provides a new, simple, and practical route to alkynyl sulfides. Abstract: A heterogeneous copper-catalyzed direct oxidative cross-dehydrogenative coupling of terminal alkynes with thiols was achieved in DMSO at 70 °C in the presence of an MCM-41-supported bidentate nitrogen copper(I) complex [MCM-41-2N-CuCl] and K2 CO3 under an atmosphere of O2, yielding selectively a variety of alkynyl sulfides in good to excellent yields. This heterogeneous copper catalyst can be easily recovered by a simple filtration and recycled 10 times without any decreases in activity.